2015
DOI: 10.1017/s136898001500169x
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Nutrition Functional Diversity indicator to assess food system contributions to dietary diversity and sustainable diets of Malawian households

Abstract: Objective: Dietary diversity is associated with nutrient adequacy and positive health outcomes but indicators to measure diversity have focused primarily on consumption, rather than sustainable provisioning of food. The Nutritional Functional Diversity score was developed by ecologists to describe the contribution of biodiversity to sustainable diets. We have employed this tool to estimate the relative contribution of home production and market purchases in providing nutritional diversity to agricultural house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 25 publications
(43 reference statements)
7
68
0
Order By: Relevance
“…Our findings of higher Wild Food Procurement and Wild Food Dietary Diversity scores being associated with lower food security scores are consistent with the literature (Luckett, DeClerck, Fanzo, Mundorf, & Rose, 2015;Powell, Thilsted, Ickowitz, Termonte, Sunderland, & Herforth, 2015). However, Wild Food Dietary Diversity was notably lower in this study than in rural communities in other parts of the world, including Asia, Africa, and South America (Bharucha & Pretty 2010;Cruz-Garcia, Caffi, Zans, & Sanchez-Choy, 2018;Shumsky et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Our findings of higher Wild Food Procurement and Wild Food Dietary Diversity scores being associated with lower food security scores are consistent with the literature (Luckett, DeClerck, Fanzo, Mundorf, & Rose, 2015;Powell, Thilsted, Ickowitz, Termonte, Sunderland, & Herforth, 2015). However, Wild Food Dietary Diversity was notably lower in this study than in rural communities in other parts of the world, including Asia, Africa, and South America (Bharucha & Pretty 2010;Cruz-Garcia, Caffi, Zans, & Sanchez-Choy, 2018;Shumsky et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Even foods that are produced on the farm may not always be stored for the entire year; issues of seasonality are particularly important for fresh fruits and vegetables ( 21 ) . Previous studies have shown that foods purchased from the market contribute considerably to farm household diets also in subsistence-oriented settings ( 19 , 20 ) . We also found that sales of maize and other crops have positive effects, because the cash income thus generated can be used to purchase diverse foods in the market.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, an important part of this literature concentrates on just one activity or aspect of the food system for example the sustainability of phosphorous [18], farm workers' health [19], organic agriculture [20], home gardens [21], meat consumption and production [22], the performance of a specific product [23] or obesity [24]. On the other hand, many works focus on just one dimension of sustainability, such as studies on planetary boundaries [25], food ecological footprints [26][27][28], or nutrition functional diversity [29]. Indeed, health and nutritional aspects are increasingly considered as a key topic in these frameworks [30], although not always in relation to all the other sustainability or food security dimensions.…”
Section: What Is Assessed?mentioning
confidence: 99%